Design of a Customer Relationship Management (CRM) Model for Small and Retail Business Zahraza Beauty Products in the Covid-19 Pandemic Era - Wahyu Eko Prasetyo; Bayu Wardhana; Hadiah Fitriyah (JPIM (Jurnal Penelitian Ilmu Manajemen), 2022)
The growth potential of the beauty product industry in Indonesia is considered very potential. The industry and trade of Indonesian beauty products is projected to increase by USD 7.5 billion with a growth of 6.5% annually for the next five years. The huge potential in the industrial business and trade in beauty products has caused many people to compete to enter this business. This of course will create intense competition among the beauty product business people. Business people are required to win in this business competition. One of the efforts that can be done is to maintain good relations with customers. Customer Relationship Management is a model that can be applied in maintaining customer relationships. The focus in this research is to design and design a model of customer relationship management in small-scale beauty products and retail businesses. The research method used in this study is a qualitative method with an observation approach